PROYEKSI OPTIMALISASI PERADILAN ELEKTRONIK SEBAGAI UPAYA PEMBANGUNAN SISTEM PAKAR (EXPERT SYSTEM - Sugeng Sulistyo, Trisoko (Ikatan Hakim Indonesia (IKAHI), 2023)
What is the projection for optimization of information technology systems, especially electronic justice based on the 2010-2035 judicial reform blueprint? and, Does an expert system have the potential to be built and integrated with electronic justice so that it can provide input for judge's judgments? the two aforementioned questions are fundamental questions which in discussion are able to provide an explanation for the public regarding the achievements of the Supreme Court in the development of electronic judicial today and provide input on how electronic justice will be developed in the future so as to be able to improve the quality of judgments. The discussion of this paper is based on the 2010-2035 blueprint and contemporary achievements in the development of electronic judicial. The results of the research indicated that i) MA is developing electronic justice according to the 2010-2035 blueprint and developing the potential E-RIS to become a knowledge database ii) Development of a knowledge database is a major potential in the development of an expert system that may assist to provide input to judge judgments. The input is in accordance with the rules of reasoning, faster and more consistent.